Calibration of boundary conditions correlated to the diffusivity of chloride ions: An accurate study for random diffusivity - Zacchei, Enrico; Gorla Nogueira, Caio [UNESP] (Elsevier, 2022)
For reinforced concrete (RC) structures, the corrosion of the reinforced steel bars from chloride ions is a periodic risk. The chloride ions diffusion is governed by Fick’ laws, however, these equations can be applied under the condition that the diffusivity is constant in the time and space. In this way, the diffusion process and the relative scenario could be greatly simplified. In this paper, a more complete non-constant multifactorial diffusivity is proposed accounting the water/cement ratio, chloride binding, temperature, age, deformation, damage, humidity. To consider a non-constant diffusivity, the use of numerical solutions is necessary. For this, Hermite polynomials (HPs) have been implemented for 1D and 2D model. Specified boundary conditions for this application have been calibrated to solve partial differential equations (PDEs) for random fluctuation diffusivity. Results show that traditional approaches bad estimate the chloride concentration for long scenarios at certain depths.
Keywords: Boundary conditions; Chloride diffusion; Concrete structures; Hermite polynomials; Non-constant diffusivity